New evidence on the information and predictive content of the Baltic Dry Index - Nicholas Apergis; James E. Payne (International Journal of Financial Studies, 2013)
This empirical study analyzes the information and predictive content of the Baltic Dry Index (BDI) with respect to a range of financial assets and the macroeconomy. By using panel methodological approaches and daily data spanning the period 1985-2012, the empirical analysis documents the joint predictability capacity of the BDI for both financial assets and industrial production. The results reveal the role of the BDI in predicting the future course of the real economy, yielding a link between financial asset markets and the macroeconomy.
Keywords: C23; G11; G12; G13; E23; 330; Baltic Dry Index; asset markets; macroeconomy; panel data